Забезпечення цифрового інтегрування логістичних потоків між підприємствами в Україні і Польщі - Касян, С. Я.; Шостек, Д. (Видавництво Львівської політехніки, 2018)
Висвітлено стратегії міжнародних маркетингових комунікацій, транснаціо- нального логістичного менеджменту, поведінки споживачів та суб’єктів господарювання у межах інтегрованих міжнародних логістичних об’єднань в економічному просторі ЄС. Окреслено основні напрямки розвитку міжнародних логістичних стратегій у бізнес-просторі, низку положень концепції маркетингу на ринку логістичних послуг, описано зміст і структуру динамічних економічних і логістичних ефектів спільного ринку країн ЄС. Обґрунтовано доцільність розвитку технологій міжнародного логістичного менеджменту в інноваційній діяльності підприємств та описано основні засади функціонування міжнародної маркетингової та логістичної складової виробничих підприємств України і Польщі. Соціально-відповідальне планування і координування міжнародних ресурсних потоків дозволяє забезпечити сучасних освічених споживачів більш інтелектуально наповненими глобальними маркетинговими цінностями в суспільному просторі, що орієнтується на інноваційні знання. Удосконалено процедуру забезпечення цифрового міжнародного інтегрування логістичних потоків між підприємствами в Україні і Польщі, що, на відміну від існуючих, базується на стратегічному узгодженні міжнародного набору маркетингу-мікс та логістики-мікс інноваційних підприємств.

In an article the international marketing communications strategy, transnational logistic management, behavior of consumers and economic subjects, within the integrated international logistic associations in the EU economic space are reflected. The main directions of the international logistic strategy development in business space, a number of the concept of marketing provisions in the market of logistic services, contents and structure of dynamic economic and logistic effects of the EU countries common market are described. It is proved expediency of the international logistic management technologies development in innovative activity of the enterprises. The basic principles of functioning of the international marketing and logistic component of manufacturing enterprises of Ukraine and Poland are described. The procedure of ensuring of digital international integration of logistic flows between enterprises in Ukraine and Poland is improved. This procedure, unlike existing, is based on strategic coordination of the international set marketing mix and logistics mix of the innovative enterprises Market impulses allow to direct logistic flows in the optimum directions that sets a positive trend to accumulation of marketing efficiency in logistics systems. In modern business interaction of the enterprises in the conditions of globalization it is necessary to conduct a system research of strategy of the international marketing communications, logistic management, behavior of consumers and economic subjects, within the integrated international logistic associations. During creation of logistic strategy it is necessary to form the high level of logistic service during long-term term, to integrate marketing communications and logistics. The organization of the international strategy and tactics of the advertising company has to be based partially on a configuration of logistic indicators, such as: updating of the commodity range, frequency of purchases in the global markets, features of storing of advertising appeals and seasonality of business. The social responsible planning and coordinating of the international resource flows allows to provide modern educated consumers with more intellectually filled global marketing values in public space. System integration of service elements in global virtual market space promotes increase in efficiency of the international logistic management of the enterprises. The behavior of economic subjects and consumers of Ukraine has to display success of their integration into the EU integrate marketing and legal space. In this regard experience of Poland is very good. It is appropriate to allocate a complex of marketing communications and logistics mix, having methodologically imposed system integration of marketing and logistics on such combination. The organization of the logistic analysis at the industrial enterprises allows to carry out in due time monitoring of consumer qualities of the international flows of goods and to extend a complex of logistic services which promotes the international integration of marketing within a logistics system. The organization of logistic analysis at the industrial enterprises allows to carry out in due time monitoring of consumer qualities of flows of goods and to extend a complex of logistic services which promotes integration of marketing within a logistics system. Optimization of participation of Ukraine and Poland in the international logistic cooperation is possible thanks to definition and development of resistant and relative competitive advantages of the states. It is necessary to refer existence of a highly skilled manpower, an advantageous geographical location to these advantages. It is displayed on coordination of the main international logistic marketing flows within united integration market space.
The ensuring of digital integration of logistic flows between enterprises in Ukraine and Poland
Keywords: транснаціональний логістичний менеджмент; економічний простір ЄС; міжнародні логістичні стратегії; міжнародне інтегрування; логістичні потоки; transnational logistic management; EU economic space; international logistic strategy; international integration; logistic flows; 339.14; 339.5.012; 339.922